Silenced LINC01134 Enhances Oxaliplatin Sensitivity by Facilitating Ferroptosis Through GPX4 in Hepatocarcinoma - Kang, Xiaofeng; Huo, Yan; Jia, Songhao; He, Fuliang; Li, Huizi; Zhou, Qing; Chang, Nijia; Liu, Donghui; Li, Rongkuan; Hu, Yi; Zhang, Ping; Xu, An (Frontiers in Oncology, 2022)
Purpose: Recently, long noncoding RNA LINC01134 has been shown to reduce cell viability and apoptosis via the antioxidant stress pathway, thereby enhancing OXA resistance in hepatocellular carcinoma. However, the association of LINC01134 with ferroptosis and the underlying molecular mechanisms remain to be elucidated. Methods: Bioinformatics analysis was employed to screen lncRNAs positively correlated with GPX4 and poor clinical prognosis. And Western blot and RT-PCR analysis in HCC cells confirmed the effect of LINC01134 on GPX4 expression. In addition, LINC01134 siRNA was transfected in HCC cells to detect the changes in cell viability, ROS, lipid peroxidation, MDA levels and GSH / GSSG levels. CCK-8, colony formation and apoptosis assays were performed to determine the effect of LINC01134 on cell death. The effect of LINC01134 and OXA on Nrf2 transcriptional binding to GPX4 was analyzed using dual luciferase reporter assay and CHIP. The expression of GPX4 and Nrf2 in HCC tissues was detected by FISH and IHC. Results: LINC01134 is a novel lncRNA positively correlated with GPx4 and associated with poor clinical prognosis. Silenced LINC01134 conferred OXA sensitivity by enhancing total ROS, lipid ROS, MDA levels and decreasing GSH / GSSG ratio. Mechanistically, LINC01134 and OXA could promote Nrf2 recruitment to the GPX4 promoter region to exert transcriptional regulation of GPX4. Clinically, LINC01134 was positively correlated with GPX4 or Nrf2, demonstrating the clinical significance of LINC01134, Nrf2 and GPX4 in OXA resistance of HCC. Conclusions: We identified LINC01134 / Nrf2 / GPX4 as a novel and critical axis to regulate HCC growth and progression. Targeting GPX4, knocking down LINC01134 or Nrf2 could be a potential therapeutic strategy for HCC.